Treatment of very high-risk classical Hodgkin Lymphoma: cases’ selection from real life and critical review of the literature - Rusconi, Chiara; Ciavarella, Sabino; Fabbri, Alberto; Flenghi, Leonardo; Puccini, Benedetta; Re, Alessandro; Sorio, Marco; Vanazzi, Anna; Zanni, Manuela (Acta Biomedica Atenei Parmensis, 2020)
Over the last 4 decades, advances in radiation therapy and the addition of combination chemotherapy have significantly increased the cure rate of patients with HL, with a 5-year OS of about 90% . However, despite high rate of cure after first line of therapy, 5%-10% of HLs are refractory to the treatment, and 10-30% of patients have a disease relapse after a complete response (CR). Relapsed HL can be treated with salvage therapies with a long-lasting complete remission in 80% of cases. In recent years, novel drugs are available for the patients with relapsed/refractory HL, like Brentuximab Vedotin and immune checkpoint inhibitors. These drugs have been able to rescue a cohort of patients who subsequently could receive an allogeneic stem-cell transplant. Our cases have been chosen because they are representative of critical issues in the management of relapsed/refractory HL; our experiences are consistent with what reported by other Authors.